Self-control duration and implicit willpower assumptions in the cognitive association between self-control and decreased vitality - Max Blaise; Alex Bertrams (Acta Psychologica)
Based on the schema model of self-control, recent research has shown that people cognitively associate self-control exertion with a subsequent decrease in perceived vitality. The present study aimed to replicate this effect and extend it by testing two additional hypotheses: greater exertion of self-control would be cognitively associated with a more pronounced decline in perceived vitality, and endorsement of a limited-resource theory would be negatively related to perceived subjective vitality in self-control situations. Participants (N = 143) read two vignettes describing a fictitious character who either exerted self-control (typing with an unfamiliar AZERTY keyboard) or did not (typing with a familiar QWERTZ keyboard). For each condition, participants rated how vital the individual would feel after 5 and 10 min. They also completed a standardized scale assessing their own implicit belief in limited versus non-limited willpower. As expected, perceived vitality was rated lower after 5 min of self-control exertion than after 10 min of no self-control (t(142) = −7.43, p < 0.001, dz = −0.62). Furthermore, the fictitious character was perceived as less vital after 10 min than after 5 min of self-control exertion (t(142) = −6.04, p < 0.001, dz = −0.51). Lastly, the more participants endorsed a limited-resource theory, the lower they rated the character's vitality following 10 min of self-control (r = −0.26, p = 0.002). Contrary to prediction, this association did not emerge in the 5-min condition (r = −0.16, p = 0.05). These findings are discussed in light of the schema model of self-control.